Pengaruh kualitas produk, persepsi harga dan promosi terhadap keputusan pembelian di denny’s restoran Senayan City - Fairliantina, Edvin; Paniroi, Jordan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine whether there is an effect of Service Quality (X1), Price Perception (X2), and Promotion (X3) on Purchase Decision (Y) partially and jointly at Denny’s Restaurant Senayan City. The number of samples in this study was 80 people using purposive accidental sampling methode. The data analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Descriptive Analysis, F Test, T Test, Correlation Coefficient Analysis and Determination (R) by using SPSS 20. Based on the results of the analysis stated that the quality of service, price perception, and promotion simultaneously have a significant influence on purchase decision at Denny’s Restaurant Senayan City. The results showed that partially the Product Quality variable had a significant effect on purchase decisions and gave a significant contribution of 1,90%, the Price Perception variable had a significant effect on purchase decisions and contributed 20,25%, the Promotion variable had an effect on purchase decisions and contributed 21,90% therefore, the variables of Product Quality, Price Perception and Promotion simultaneously affect Purchase Decisions at Denny’s Restaurant Senayan City by 79,92%.